Education and cultural heritage: town and country as identity settings (Tempo e Argumento, 2011)
The paper aims at relating popular education, cultural heritage, town and country, putting together studies on material and intangible culture aspects. It also aims at contributing to fostering innovative practices and knowledge about memory settings, such as museums, including social movements and popular education. The paper also addresses concepts such as ways of life, sometimes forgotten and almost invisible in the mainstream documents and “official” material culture collections and exhibitions. The paper then explores relations, contradictions and a plethora of collective and personal exchanges, showing how unexpected issues relating to heritage and popular education can prove useful and fruitful.
Keywords: education; heritage; countryside; town